First‐in‐Human, Healthy Volunteers Integrated Protocol of ETC‐206, an Oral Mnk 1/2 Kinase Inhibitor Oncology Drug - Vincenzo Teneggi; Veronica Novotny‐Diermayr; Lay Hoon Lee; Maryam Yasin; Pauline Yeo; Kantharaj Ethirajulu; Sylvia Bong Hwa Gan; Stephanie E. Blanchard; Ranjani Nellore; Dhananjay N. Umrani; Roberto Gomeni; Darren Lim Wan Teck; et al. (Wiley, 2020)
In the last decade, drug development has tackled substantial challenges to improve efficiency and facilitate access to innovative medicines. Integrated clinical protocols and the investigation of targeted oncology drugs in healthy volunteers (HVs) have emerged as modalities with an increase in scope and complexity of early clinical studies and first‐in‐human (FIH) studies in particular. However, limited work has been done to explore the impact of these two modalities, alone or in combination, on the scientific value and on the implementation of such articulated studies. We conducted an FIH study in HVs with an oncology targeted drug, an Mnk 1/2 small molecule inhibitor. In this article, we describe results, advantages, and limitations of an integrated clinical protocol with an oncology drug. We further discuss and indicate points to consider when designing and conducting similar scientifically and operationally demanding FIH studies.